Bio-ethical principles of medical law with an emphasis on the law of Iran - Mohammad Ali Mahdavi Sabet; Sajjad Mazloumi (Juridical Tribune, 2016)
There has been many talks about the necessity of ethics in all affairs, especially medical affairs which deal with the lives of individuals and the society expects Medical Group to be abide by morals more than laws. This matter indicates on the fact that the society considers ethics as a stronger enforcement of the law and deplores a doctor who has ignored ethics in the medical profession. Thus, they blamed the doctor from ethical aspect more than deploring him from a legal aspect (civil or criminal liability). The legislator is also influenced by public in anticipation of responsibility (both criminal and civil) for doctors and imposes legal rules on this basis. The concept of this article has an extremely close relationship with three concepts of morality, professional ethics and law. Initially first two concepts will be defined and separated and then the relation between professional ethics and medical laws will be expressed. Then, the relation between two concepts of medical ethics and bioethics ethics will be evaluated. Two religion or secularism basis have been taken for medical rights and strengths and weaknesses of each are discussed and the approach of the Iranian legal system will also be mentioned with evaluation of controversial medical samples.